2019
DOI: 10.1115/1.4045272
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fan Root Flow on the Aerodynamic of a Low-Pressure Compressor Transition Duct

Abstract: To reduce fuel-burn and emissions, there is a drive toward higher bypass ratio and smaller high-pressure ratio core engines. This makes the design of the ducts connecting compressor spools more challenging as the higher radius change increases aerodynamic loading. This is exacerbated at inlet to the engine core by fan root flow which is characterized by a hub-low-pressure profile and large secondary flow structures. Additionally, shorter, lighter nacelles mean that the intake may not provide a uniform inlet fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The slower hub speed of large fan blades and secondary flows generated at the hub typically give rise to a hublow total pressure profile at rotor exit. Walker et al [1] investigated the effect of such a profile compared to a nominally flat profile and observed an increase in overall duct loss. However, they also observed modified secondary flows through the ESS which promoted momentum exchange between the core flow and the hub boundary layer.…”
Section: Rolls-royce Plcmentioning
confidence: 99%
See 3 more Smart Citations
“…The slower hub speed of large fan blades and secondary flows generated at the hub typically give rise to a hublow total pressure profile at rotor exit. Walker et al [1] investigated the effect of such a profile compared to a nominally flat profile and observed an increase in overall duct loss. However, they also observed modified secondary flows through the ESS which promoted momentum exchange between the core flow and the hub boundary layer.…”
Section: Rolls-royce Plcmentioning
confidence: 99%
“…Flow field data in the duct suggested this moved the duct further from separation and that potentially a shorter, more aggressive duct could be used. However, the experimental configuration used by Walker et al [1] did not produce representative rotor secondary flows and loss cores. Hence Tsakmakidou et al [12] built on the work by numerically examining the parameters which affect the generation of secondary flows through the rotor.…”
Section: Rolls-royce Plcmentioning
confidence: 99%
See 2 more Smart Citations
“…-Turning strut could not remove swirl completely, hence, some sort of secondary flows were found at duct outlet. Walker et al [98] Incorporated the engine suction splitter (EES) -ESS showed a very small effect on flow development and due to wakes produced by ESS, flow did not move towards the separation. -The rapid mixing of wakes enhanced the duct loss by 12%.…”
Section: Integrated Conceptmentioning
confidence: 99%